Advances in Self-Organizing Maps 8th International Workshop, WSOM 2011, Espoo, Finland, June 13-15, 2011. Proceedings - Laaksonen, Jorma; Honkela, Timo (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 8th International Workshop on Self-Organizing Maps, WSOM 2011, held in Espoo, Finland, in June 2011. The 36 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on plenaries; financial and societal applications; theory and methodology; applications of data mining and analysis; language processing and document analysis; and visualization and image processing.